African Music Creativity and Performance: The Science of the Sound - Nzewi, Meki (Voices: A World Forum for Music Therapy, 2006)
What we believe we see or hear is often far from the truth of what we are seeing or hearing. What we know we feel is often merely a sign of what we do not know is happening to us. Without cognitive understanding, what we do with extant indigenous knowledge manifestations will be abstracted misrepresentations and misimpressions that problematize contemporary advancement and re-deployment in initiatives.